If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(5x + -2) = 6(6x + -1) * x Reorder the terms: 7(-2 + 5x) = 6(6x + -1) * x (-2 * 7 + 5x * 7) = 6(6x + -1) * x (-14 + 35x) = 6(6x + -1) * x Reorder the terms: -14 + 35x = 6(-1 + 6x) * x Reorder the terms for easier multiplication: -14 + 35x = 6x(-1 + 6x) -14 + 35x = (-1 * 6x + 6x * 6x) -14 + 35x = (-6x + 36x2) Solving -14 + 35x = -6x + 36x2 Solving for variable 'x'. Combine like terms: 35x + 6x = 41x -14 + 41x + -36x2 = -6x + 36x2 + 6x + -36x2 Reorder the terms: -14 + 41x + -36x2 = -6x + 6x + 36x2 + -36x2 Combine like terms: -6x + 6x = 0 -14 + 41x + -36x2 = 0 + 36x2 + -36x2 -14 + 41x + -36x2 = 36x2 + -36x2 Combine like terms: 36x2 + -36x2 = 0 -14 + 41x + -36x2 = 0 Begin completing the square. Divide all terms by -36 the coefficient of the squared term: Divide each side by '-36'. 0.3888888889 + -1.138888889x + x2 = 0 Move the constant term to the right: Add '-0.3888888889' to each side of the equation. 0.3888888889 + -1.138888889x + -0.3888888889 + x2 = 0 + -0.3888888889 Reorder the terms: 0.3888888889 + -0.3888888889 + -1.138888889x + x2 = 0 + -0.3888888889 Combine like terms: 0.3888888889 + -0.3888888889 = 0.0000000000 0.0000000000 + -1.138888889x + x2 = 0 + -0.3888888889 -1.138888889x + x2 = 0 + -0.3888888889 Combine like terms: 0 + -0.3888888889 = -0.3888888889 -1.138888889x + x2 = -0.3888888889 The x term is -1.138888889x. Take half its coefficient (-0.5694444445). Square it (0.3242669754) and add it to both sides. Add '0.3242669754' to each side of the equation. -1.138888889x + 0.3242669754 + x2 = -0.3888888889 + 0.3242669754 Reorder the terms: 0.3242669754 + -1.138888889x + x2 = -0.3888888889 + 0.3242669754 Combine like terms: -0.3888888889 + 0.3242669754 = -0.0646219135 0.3242669754 + -1.138888889x + x2 = -0.0646219135 Factor a perfect square on the left side: (x + -0.5694444445)(x + -0.5694444445) = -0.0646219135 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 16=7x-33 | | -1+5y=-16 | | 5r^2-44r+120=-30+111r | | -9+6b=9+3b | | 36+(24)3= | | -15=6+7y | | 4x+5+5x+22=90 | | (X/5)=-13 | | 4k=6k-6 | | 4k=6k-2 | | 48.3(8/25)2 | | a+2=-12 | | 3y+2=y+11 | | 4x^2-32x+20=0 | | 7-4s-1=-3s-4 | | 9y+5x=37 | | -2x+49=2x+13 | | -4h=40 | | -2+17-5=0 | | -3x+1=x+13 | | -6-4g=10-2g | | 9=(v/7) | | 2(-2x+17)=0 | | -5=2y+1 | | 16=0.5X+6 | | =9-5 | | 9=2+b | | 2(-2-4p)+2(-2p-1)=0 | | 12=-4+y | | 6x=(x+2)8+6 | | -11=-2+-1y | | (v/6)=13 |